2007
DOI: 10.1074/jbc.m604732200
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Macromolecules in Hard Tissues Control the Nucleation and Hierarchical Assembly of Hydroxyapatite

Abstract: Biogenic minerals found in teeth and bones are synthesized by precise cell-mediated mechanisms. They have superior mechanical properties due to their complex architecture. Control over biomineral properties can be accomplished by regulation of particle size, shape, crystal orientation, and polymorphic structure. In many organisms, biogenic minerals are assembled using a transient amorphous mineral phase. Here we report that organic constituents of bones and teeth, namely type I collagen and dentin matrix prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
238
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(251 citation statements)
references
References 37 publications
8
238
1
4
Order By: Relevance
“…matrix-specific precipitation of calcium phosphate on its own but relies on several different noncollagenous proteins that control nucleation and initial progression of mineralization. 31,32,45,107 In contrast, enamel mineralization takes place within a noncollagenous protein matrix that is secreted by ameloblasts of epithelial origin. This enamel matrix consists of specialized proteins that regulate the structural development and mineralization of enamel.…”
Section: Discussionmentioning
confidence: 99%
“…matrix-specific precipitation of calcium phosphate on its own but relies on several different noncollagenous proteins that control nucleation and initial progression of mineralization. 31,32,45,107 In contrast, enamel mineralization takes place within a noncollagenous protein matrix that is secreted by ameloblasts of epithelial origin. This enamel matrix consists of specialized proteins that regulate the structural development and mineralization of enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the obvious differences in their biochemical features, it is logical to hypothesize that these variants may have distinct functions and play different roles in biomineralization. In vitro mineralization studies have demonstrated that the COOH-terminal fragment promotes mineralization by acting as a nucleator for hydroxyapatite formation [14][15][16]. Information regarding the biological functions of the NH 2 -terminal fragment and DMP1-PG is lacking.…”
mentioning
confidence: 99%
“…Some successful methods including emulsion, 39,40 hydrothermal method, 41,42 solvothermal method, 43 sonochemical precipitation, 44 hard-template method, 45 sol-gel method, 46 biomimetic method, 47,48 and microwave irradiation 49 have been employed in the synthesis of HA. Gajjeraman et al 50 used organic constituents of bones and teeth to control the nucleation and assembly of hierarchical HA. Wang et al 51 reported the fabrication of HA nanorods by tuning the interfaces between surfactants and the central atoms of HA based on the liquid-solid-solution mechanism.…”
Section: Introductionmentioning
confidence: 99%